Systematic literature Review: Implementasi Model Evaluasi CIPP (Context, Input, Proses, dan Product) dalam Kurikulum Merdeka - Muflih Nurriza Pahlawi; Nurfuadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Change process curriculum appear on base diverse needs​ and on the main thing is leads on need public as user product school. Current curriculum​ this used is curriculum independent that is system focused curriculum​ on realm interest And talent student. Interesting see implementation of the CIPP evaluation model in curriculum independent because of this model own components consisting​ from four aspect that is context, input, process, and product. Study This use type approach literature review which is a process of searching, evaluating, and linkages between relevant references​ or in accordance with topic study related. Results study this is Evaluation curriculum independent using the CIPP model started from aspect evaluation context, input, process, up to product. Evaluation context as material identification related conditions, issues, etc possible obstacles​ there is in environment an educational program implemented, evaluated input become answer on difficulties experienced​ related strategy and method utilise source power, process evaluation has objective as material evaluation implementation curriculum independent as well as interaction student and teachers in the learning process, and evaluation product refer on intended result​ from application curriculum independent.